2018
DOI: 10.1111/epi.14586
|View full text |Cite
|
Sign up to set email alerts
|

Imaging biomarkers of behavioral impairments: A pilot micro–positron emission tomographic study in a rat electrical post–status epilepticus model

Abstract: Objective:In patients with epilepsy, psychiatric comorbidities can significantly affect the disease course and quality of life. Detecting and recognizing these comorbidities is central in determining an optimal treatment plan. One promising tool in detecting biomarkers for psychiatric comorbidities in epilepsy is positron emission tomography (PET). Methods: Behavioral and biochemical variables were cross-correlated with the results from two μPET scans using the tracers [ 18 F]fluoro-2-deoxy-D-glucose ([ 18 F]F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
2
9
1
Order By: Relevance
“…In addition, behavioral test batteries in the electrical post-SE and other epilepsy models can be used to assess correlations between potential biomarker candidates and behavioral parameters under standardized conditions. 38,39 Finally, we were eager to obtain further information about whether replacement of tethered seizure monitoring by telemetric seizure monitoring reduces the burden for the animals as suggested by Lidster et al 2 Our findings from the pilocarpine model revealed that minor differences can be observed between animals with tethered and telemetric recordings with evidence for a higher level of distress in the group with tethered monitoring (Koska et al, manuscript in revision).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, behavioral test batteries in the electrical post-SE and other epilepsy models can be used to assess correlations between potential biomarker candidates and behavioral parameters under standardized conditions. 38,39 Finally, we were eager to obtain further information about whether replacement of tethered seizure monitoring by telemetric seizure monitoring reduces the burden for the animals as suggested by Lidster et al 2 Our findings from the pilocarpine model revealed that minor differences can be observed between animals with tethered and telemetric recordings with evidence for a higher level of distress in the group with tethered monitoring (Koska et al, manuscript in revision).…”
Section: Discussionmentioning
confidence: 83%
“…The data used in this study was originally published in five individual studies, investigating three different rat epilepsy models [12][13][14][15][16]. A total of seven subprojects were carried out.…”
Section: Animalsmentioning
confidence: 99%
“…Chemical post-status epilepticus model [15,16]. Following a three week recovery period animals were injected with lithium chloride (i.p.…”
Section: Surgery and Epilepsy Modelsmentioning
confidence: 99%
See 2 more Smart Citations